Taguchi analysis of dissimilar aluminum sheets joined by friction stir spot welding - (:unkn) unknown (PAMUKKALE UNIV, 2016)
In recent years, the welding of materials of new and complex structure constitutes a problem for the industry. The solid state welding method for joining of these materials were effective. Sheets produced from aluminum and aluminum alloys, especially in areas such as automotive, railway and defense industry have revealed the requirement of the application of solid state welding methods. The friction stir spot welding is one of the solid state welding method. Welding parameters is very important FSSW in order to obtain the maximum welding strength in FSSW. SKNK as parameters (tool rotational speed, depth, dive team, team and team inclination angle of standby time) is selected. In this study has investigated the joining of AA2024-T3 and AA5754-H22 aluminum alloy sheets with FSSW technique by Taguchi analysis. The highest -the better quality control characteristic using the Analysis of Variance (ANOVA) method were obtained the optimum welding parameters. The results have been analyzed both the graphical methods and numerical data. The most important parameters affecting the weld tensile strength were detected as tool rotation speed (44.74%) and the team of waiting time (31.60%). Weld tensile strength by Taguchi analysis result conducted for comparing experiments the increased by 42% compared to the initial parameters.
Keywords: Friction stir spot welding; Mechanical properties; Taguchi method; Optimization; MECHANICAL-PROPERTIES; PARAMETERS; OPTIMIZATION; GEOMETRY; ALLOY